# Some equations from Russian maths book. [closed]

Could you please help me with solving these equations. I would like to solve them in the most sneaky way. All of the exercises in this book can be solved in some clever way which I can't often find.

$$\frac{(x-1)(x-2)(x-3)(x-4)}{(x+1)(x+2)(x+3)(x+4)} = 1$$ $$\frac{6}{(x+1)(x+2)} + \frac{8}{(x-1)(x+4)} = 1$$ $$\sqrt[7]{ (ax-b)^{3}} - \sqrt[7]{ (b-ax)^{3} } = \frac{65}{8}; a \neq 0$$

-

## closed as off-topic by heropup, Grigory M, Morgan Rodgers, Did, user 170039Jan 9 at 14:59

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – heropup, Grigory M, Morgan Rodgers, Did, user 170039
If this question can be reworded to fit the rules in the help center, please edit the question.

Just curious -- which book is this? – Dejan Govc Jan 8 at 19:00
I've compared this with the original book. The third equation is misstated. The exponent in the second root is supposed to be $-3$, not $3$. – David Jan 8 at 20:42
@DejanGovc For the sake of completeness: it's a problem book for high school students wishing to go to a technical college (ed. Skanavi). – TT_ Jan 8 at 21:16
Why was this even upvoted, let alone on HNQ? It looks like an obvious homework question, and the OP didn't even show much (if any) effort. – March Ho Jan 9 at 4:34
Transcription of the title from the cover you posted: Сканави М.И. Сборник задач по математике для поступающих во ВТУЗЫ. English transcription: Skanavi M.I. (red.) Sbornik zadach 1 po matematike dlja postupajushchih vo vtuzy. Just in case it helps you if you plan to look for the book @DejanGovc – Martin Sleziak Jan 9 at 14:14

## 5 Answers

1) $\frac{(x-1)(x-2)(x-3)(x-4)}{(x+1)(x+2)(x+3)(x+4)}=1\implies\frac{(x^2-5x+4)(x^2-5x+6)}{(x^2+5x+4)(x^2+5x+6)}=1$

$\implies(x^2-5x+4)(x^2-5x+6)=(x^2+5x+4)(x^2+5x+6)$

We know that the even-indexed terms will cancel out because the LHS is just the RHS with $x\to-x$

$\implies-10x^3-50x=10x^3+50x\implies10x^3+50x=0\implies10x(x^2+5)=0\implies x=0$

2) Note that the denominators of these can be written as $u+2,u-4$ with $u=x^2+3x$. We see:

$\frac{6}{u+2}+\frac{8}{u-4}=1\implies\frac{6}{u+2}-3+\frac{8}{u-4}+2=1-3+2\implies\frac{-3u}{u+2}+\frac{2u}{u-4}=0$

Remove a factor of $u$ and accept $u=0$ as a solution. Then clear fractions:

$\frac{-3}{u+2}+\frac{2}{u-4}=0\implies-3(u-4)+2(u+2)=0\implies16-u=0\implies u=16$

So, $x^2+3x=0, 16$ - we extract $x=0,-3$ for $u=0$ and solve the $u=16$ case with the quadratic formula / your method of choice.

3) Let $(ax-b)^{3/7}=u$, then $u-(-u)=65/8\implies u=65/16$. Nowhere further to go as $a,b$ aren't given - can say $x=(65/16+b)/a$ if you'd like, I suppose.

Perhaps worth noting that $\frac{65}{8}=8+\frac{1}{8}$, as an aside.

-
Thank you so much for your anwser. I'm going to analyze it precisely :) – Jatimir Jan 8 at 19:08
No worries at all - take your time. With these tricky problems, always keep an eye out for a clever substitution or a symmetry - they tend to be the things that cut a question in half for you. – πr8 Jan 8 at 19:09
Yes, when solving exercises from this book I always try to keep and eye for it, but I'm not that good at maths. I have recently started to practice more, but I have often problems with these exercises. I attend some maths classes and I have to finish like 10 pages from this book for the next week :) Next pages look frightening to me. On the few pages there are like 5 equations per page, because they are so elaborate. – Jatimir Jan 8 at 19:18
No need to multiply numerator/denominator to note the clever symmetry. – vonbrand Jan 8 at 19:47
In part 1)? I suppose so, though it doesn't seem like it'd be markedly faster/slower to keep it as a fraction. – πr8 Jan 8 at 19:50

For the first one, consider the equation as $$\frac{f(x)}{g(x)}=1$$ However $$f(-x)\equiv g(x)$$

Therefore $f$ and $g$ are reflections of each other in the $y$ axis.

Neither has symmetry in the $y$ axis, and neither have roots of the form $x=\pm a$, so the only intersection is on the $y$ axis, so $x=0$ is the only solution.

-
I don't understand this proof. An equation $f(x) = f(-x)$ can have solutions $x \ne 0$, even when $f$ isn't an even function. For example, $f(x) = x^3 - x$ isn't even, but $x = 1$ satisfies $f(x) = f(-x)$. – David Jan 8 at 20:29
Fair point, so I have edited my answer. Thanks. – David Quinn Jan 8 at 21:00
I'm don't see why the statement "neither of them have roots of the form $x = \pm a$ is any easier than the original problem. Surely this requires proof. – David Jan 8 at 22:27
What a clever solution without drowning in details. – whatever Jan 9 at 12:08

The first equation implies that the product of the distances from $x$ to $-1, -2, -3, -4$ is the same as the product of the distances from $x$ to $1, 2, 3, 4$. (This condition is equivalent to the quotient appearing in the equation being $\pm 1$.) If $x > 0$, the latter distances are smaller than the corresponding former ones, so the latter product is smaller. If $x < 0$, then the former is. So the only possibility is $x = 0$.

In the second equation, make the substitution $u = x^2 + 3x$.

For the third one, you were almost there with what you wrote in the comments. But remember that $\sqrt[7]{-A} = - \sqrt[7]{A}$. You get $(ax - b)^{3/7} = 65/16$. Raise both sides of the equation to the power of $7/3$.

Edit The third equation has a typo in it. It was supposed to read $$\sqrt[7]{ (ax-b)^{3}} - \sqrt[7]{ (b-ax)^{-3} } = \frac{65}{8}.$$ In this case, Write $u = (ax-b)^{3/7}$. Then the equation becomes $u + 1/u = 65/8$. Since after clearing denominators this becomes a quadratic equation, there are at most two possibilities for $u$. Since $u = 8$ and $u = 1/8$ work, these must be the ones. We get $ax - b \in \{128, 1/128\}$, after which it's easy to solve for $x$.

-
Very nice, David: +1. How did you get access to the book ? – Georges Elencwajg Jan 9 at 10:49
@GeorgesElencwajg Thanks. Jatimir gave a link to it in the comments to his question. – David Jan 9 at 15:20
Thanks for the comment, David. I'm impressed by the difficulty and the sheer number of those problems. I wonder how many technical colleges in the world could ask such exercises at an entrance examination... – Georges Elencwajg Jan 9 at 19:23

First question:

Let $y=(x-2)(x-3)$. So it's equivalent to

$$\frac{y(y-2)}{(y+10x)(y+10x-2)}=1$$ $$y^2-2y=y^2+20xy+100x^2-2y-20x=0$$ $$20x=100x^2+20xy$$

For $x\neq 0$, $$1=5x+(x-2)(x-3)$$ $$x^2=-5$$ $$x=\pm\sqrt{5} i$$

Otherwise $x=0$.

-
thank you for your anwser. I understood :) – Jatimir Jan 8 at 19:30

factorizing the left minus the right-hand side we get $$-\frac{20 x \left(x^2+5\right)}{(x+1) (x+2) (x+3) (x+4)}=0$$ can you proceed from here? making the same with the second equation we get $$-\frac{x (x+3) \left(x^2+3 x-16\right)}{(x-1) (x+1) (x+2) (x+4)}=0$$

-
Can you explain how you arrived at the expressions? – Airdish Jan 8 at 18:47
Thank you for your anwser. In the first equation in numerator I have: $$(x-1)(x-2)(x-3)(x-4)-(x+1)(x+2)(x+3)(x+4)$$ is there any other way than multiplying all the brackets and simplify? – Jatimir Jan 8 at 18:50